2012
DOI: 10.1586/erc.12.157
|View full text |Cite
|
Sign up to set email alerts
|

The complex puzzle underlying the pathophysiology of acute coronary syndromes: from molecular basis to clinical manifestations

Abstract: Acute coronary syndromes (ACS) still represent a major cause of death in Western countries; in the vast majority of cases, coronary atherosclerosis represents the common pathological lesion to all forms of ACS. It is currently believed that plaque complication (rupture, fissuration, and so on), with the consequent superimposed thrombosis, is a key factor ultimately leading to the clinical occurrence of ACS. Over the last two decades, our understanding of the basic mechanisms involved in the pathophysiology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 103 publications
0
18
0
Order By: Relevance
“…The most common cause of ACS is the rupture of a ‘vulnerable' atherosclerotic coronary plaque. Other coronary events, such as coronary embolism, coronary vasospasm, drug ingestion or spontaneous coronary artery dissection, also contribute to a reduction in coronary blood flow, causing myocardial ischemia [21,22]. If the episode of myocardial ischemia is temporary, cardiac symptoms are present transiently and serologic evidence of myonecrosis is absent, leading to a diagnosis of unstable angina.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of ACS is the rupture of a ‘vulnerable' atherosclerotic coronary plaque. Other coronary events, such as coronary embolism, coronary vasospasm, drug ingestion or spontaneous coronary artery dissection, also contribute to a reduction in coronary blood flow, causing myocardial ischemia [21,22]. If the episode of myocardial ischemia is temporary, cardiac symptoms are present transiently and serologic evidence of myonecrosis is absent, leading to a diagnosis of unstable angina.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary thrombosis generally occurs at sites of a preexisting atherosclerotic plaque often precipitated by fissuration or ulceration of the plaque [1]. Several studies have identified both TF antigen and activity within human atherosclerotic plaques and have suggested that they might represent an important determinant of thrombogenicity Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we have investigated how ROS affect a cell population never investigated before in this context and that is known to be a primary source of TFPI such as HCAECs [18]. This is an important pathophysiological issue since at the endothelial cell surface, a dynamic interaction exits between mechanisms inhibiting and promoting activation of coagulation [1,2]. Unperturbed endothelial cells physiologically produces several chemical mediators, including TFPI, able to inhibit intravascular thrombus formation [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute coronary syndrome (ACS) arises from the formation of thrombus at damaged atherosclerotic plaques in coronary arteries [1][2][3][4][5][6][7][8][9][10][11]. Acute coronary syndrome is a complex disease determined by both genetic and environmental issues.…”
Section: Introductionmentioning
confidence: 99%